2008
DOI: 10.2478/s11532-008-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of tetraanionic porphyrin in formamide colloids of layered double hydroxides

Abstract: Formamide colloidal suspensions of layered double hydroxides (LDHs) with anionic dye, meso-tetrakis(4-sulfonatophenyl)porphine (TPPS) were prepared. Optical properties of these suspensions were investigated by means of absorption and fluorescence spectroscopies in the visible region. For more detailed characterization, second derivative curves of the spectra were calculated. The adsorption of the dye on LDH nanosheets led to partial molecular aggregation, reflected in significant changes of the dye optical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The Soret band of PdTPPS in the Mg 2 Al‐LDH‐DS/PdTPPS films is also slightly broadened, and the Q(1,0) band is redshifted by 3 nm relative to the absorption spectrum of monomeric PdTPPS in aqueous solution. In comparison, the aggregates of TPPS in solution,25,26 in the mesopores of MCM‐41,27 or on the surface of LDH nanosheets28 are characterized by profound shifts and broadening of the absorption bands; these features were not observed with the films. The results for the films are similar to those reported for Mg 2 Al‐LDH‐PdTPPC,29 Zn R Al‐LDH‐ZnTPPS and Mg R Al‐LDH‐TPPS ( R = 2 or 4),13,29,30 and Zn R Al‐LDH‐PdTPPC ( R = 2 or 4)31 hybrids (Figure 5).…”
Section: Structural Aspectsmentioning
confidence: 96%
“…The Soret band of PdTPPS in the Mg 2 Al‐LDH‐DS/PdTPPS films is also slightly broadened, and the Q(1,0) band is redshifted by 3 nm relative to the absorption spectrum of monomeric PdTPPS in aqueous solution. In comparison, the aggregates of TPPS in solution,25,26 in the mesopores of MCM‐41,27 or on the surface of LDH nanosheets28 are characterized by profound shifts and broadening of the absorption bands; these features were not observed with the films. The results for the films are similar to those reported for Mg 2 Al‐LDH‐PdTPPC,29 Zn R Al‐LDH‐ZnTPPS and Mg R Al‐LDH‐TPPS ( R = 2 or 4),13,29,30 and Zn R Al‐LDH‐PdTPPC ( R = 2 or 4)31 hybrids (Figure 5).…”
Section: Structural Aspectsmentioning
confidence: 96%
“…[39][40][41] It has been reported that the dispersity and stability of organic molecules can be highly improved aer their intercalation into LDH interlamellar gallery. [42][43][44] Moreover, LDHs have also been investigated as drug nanocarriers due to their low toxicity, enhanced cellular uptake and good biodegradation. [45][46][47] This motivates us to co-intercalate photothermal molecule (indocyanine green, ICG) and targeting agent (folic acid, FA) into the interlayer of LDH, so as to obtain a new targeted photothermal agent used in PTT, which would exhibit the following advantages: (i) the host-guest interactions would improve the stability of ICG, extend half-life period and thus increase the efficiency of photo-thermal transformation; (ii) the organic-inorganic composite structure promotes the hydrophilicity and biocompatibility of ICG, leading to an enhancement in drug permeability/retention.…”
Section: Introductionmentioning
confidence: 99%